1998
DOI: 10.21236/ada440725
|View full text |Cite
|
Sign up to set email alerts
|

Single Display Groupware: A Model for Co-Present Collaboration

Abstract: We introduce a model for supporting collaborative work between people that are physically close to each other. We call this model Single Display Groupware (SDG). In this paper, we describe this model, comparing it to more traditional remote collaboration. We describe the requirements that SDG places on computer technology, and our understanding of the benefits and costs of SDG systems. Finally, we describe a prototype SDG system that we built and the results of a usability test we ran with 60 elementary school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
201
0
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(206 citation statements)
references
References 8 publications
2
201
0
3
Order By: Relevance
“…Advances in single display groupware (SDG) technology (Stewart et al, 1999), have enabled the development of collaborative search systems for the co-located environment. The advantages of such systems are that they improve the awareness of collaborating searchers by bringing them together in a face-to-face environment.…”
Section: Synchronous Co-located Collaborative Information Retrievalmentioning
confidence: 99%
“…Advances in single display groupware (SDG) technology (Stewart et al, 1999), have enabled the development of collaborative search systems for the co-located environment. The advantages of such systems are that they improve the awareness of collaborating searchers by bringing them together in a face-to-face environment.…”
Section: Synchronous Co-located Collaborative Information Retrievalmentioning
confidence: 99%
“…However with large shared displays it is difficult to have equal collaboration when only one of the users has the input device, or the software doesn't support parallel input. In recent years, Stewart et al coined the term Single Display Groupware (SDG) to describe groupware systems which support multiple input channels coupled to a single display [6]. They have found that SDG systems eliminate conflict among users for input devices, enable more work to be done in parallel by reducing turn-taking, and strengthen communication and collaboration.…”
Section: Related Workmentioning
confidence: 99%
“…Researchers in Computer Supported Cooperative Work (CSCW) are now paying considerable attention to the design of single display groupware (SDG) i.e., applications that support the work of co-located groups over a physically shared display [16]. Our own work in SDG began with an investigation of transparent menus as an interaction technique that would minimize how people working close together would interfere with each other [19].…”
Section: Toolkits For Single Display Groupwarementioning
confidence: 99%